A oralidade na Educação de Jovens e Adultos: possibilidades pedagógicas a partir da linguagem teatral - Araújo , Jussara Queiroz de (2024)
The silencing of students from Educação de Jovens e Adultos (Youth and Adult Education) during Portuguese Language classes resonates with low self-esteem and insecurity. Based on this perception, we sought to find ways to reverse this silencing and provide students with situations of protagonism through theatrical language. Our main goal was to understand how the orality of students in cycle III (6th and 7th grade) of EJA could be improved when using theatrical language as a pedagogical tool. As specific goal, we sought revisiting what studies and researches say about orality; We diagnosed which abilities students of cycle III (6th and 7th grade) from Educação de Jovens e Adultos (Youth and Adult Education) had; analyzing how the pedagogical work, through theatrical language, could develop skills with regard to orality; Finally, we proposed a didactic-pedagogical material. This work was an action-research with an interventionist nature, the approach to be used was qualitative, the data generation methodology consisted of participant observation, pedagogical workshops and conversation circles, as well as the interpretation of the data took place through meaning cores. The research was based on three thematic axes. The first axis was orality, theorized by Carvalho and Ferrarezi Jr. (2018), Bakhtin (2006; 2008), Dolzs and Schnewly (2004), Bueno (2008), Ong (1998) and Marcuschi (1996; 2001; 2007). The second axis was about Educação de Jovens e Adultos (Youth and Adult Education), we used the authors: Gadotti (2021), Ferreyra (1998), Miranda (2011), Jardilino and Araújo (2015). The third and last axis consisted of theatrical language and was based on the authors: Boal (2019; 1996), Mamet (2014), Grazioli (2008), Neves and Santiago (2016) among others. In addition to the scholars mentioned above, we used the following legal provisions: Constituição Federal do Brasil (1988), Lei de Diretrizes e Bases da Educação Nacional (1996), PCN (1998), BNCC (2018), CEB/CNE resolution nº 11 /2000, Resolution nº. 7/2010, Resolution nº. 01/2021 and CNE/CP Resolution nº. 1/2021. From this research, based on the meaning cores, we were able to verify that it is possible to improve the production of oral genres, in students from cycle III (6th and 7th grade) of Educação de Jovens e Adultos (Youth and Adult Education) and that the teachable dimensions of orality are objects of knowledge which have the capacity to positively affect the quality of life and self-esteem of students. Considering this perspective, we emphasize that the teaching of orality, through theatrical language, visibly contributed to the changing in students' attitudes in their speech acts, as well as their interpersonal relationships inside and outside the school space. We also observed, in their statements and attitudes throughout the process, that the practice of speaking fostered the unity of the group (students and teacher) and self-confidence in communicating with co-workers, family and friends.Concomitantly with these results and findings, we developed a didactic-pedagogical book titled: Oralizarte: possibilidades pedagógicas com a oralidade na EJA por meio da linguagem teatral (Oralizart: pedagogical possibilities with orality in EJA through theatrical language); material that aims to suggest ways and assist Portuguese language teachers with new ideas and perspectives on teaching speaking through theatrical games.